THE ROLE OF LEGAL DISCOURSE IN MODERN LINGUISTICS - Rakhmatova, Bahara (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
In this article, the role of legal discourse in modern linguistics and its connection with other areas of linguistics is highlighted. Although the concept of legal discourse is not new in science, it is important to study it deeply from the linguistic point of view. Because it is one of the types of discourse that has not been thoroughly studied in linguistics, despite the fact that it is separated from political discourse. Based on the definitions given in the article, we can say that recently, the development of internal statehood in the world civilization, the rule of law in society is increasing, the demand for legal language and legal literacy is also increasing. Sometimes universally recognized concepts are updated and refined over the years in the process of globalization. This means the task of gaining a deep understanding of legal discourse, including legal discourse. Based on this, it should be said that the history of discourse, its origin, and the role of legal discourse in general linguistics are covered in detail in this study. It is noted that this type of discourse is closely related to many aspects of the linguist, so it is stated that the task of studying it is also important. In addition, special features of the legal discourse are also discussed.